Telaah Filosofi Surah Al-Fatihah dalam Perspektif Psikologi dan Manajemen Pendidikan era Revolusi Industri 4.0 - Al-Mahali, Ahmad Mustofa Jalalluddin (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
At present, very little of what children in schools do is really taken into account their technological abilities which in fact are digital natives that cannot be taught in conventional ways. Conventional education institutions, especially Islamic based institutions, are many who experience confusion in this matter. in this perspective Penilis tried to take part in dealing with this problem by raising the first surah from the Qur'an. Al-Fatihah as Al-Shifa (The Cure) gives protection to Satan and his followers and strengthens the human heart towards the first. Al-Kanz (Treasure) indicates that the surah is a storehouse of endless knowledge which is an abstract document of the Koran. It is not difficult to understand when Qutb carefully notes that the Qur'an presents Islam as